An Unusual Position for the Permanent Pacing Wire - Mishra, Pankaj Kumar; Ng, Alexander; Luckraz, Heyman (The Thoracic and Cardiovascular Surgeon Reports, 2014)
Complications related to permanent pacing wires insertion include ventricular perforation. It commonly perforates the right ventricle. We present images of an unusual case where the pacing wires perforated the anterior left ventricular wall between the left anterior descending artery and diagonal artery.
Keywords: permanent pacing wires; left ventricular perforation; artery